Effectiveness of social capital in the job search process - Ralf Werner Koßmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
The empirical literature has provided ample yet contradictory evidence on the effectiveness of social ties in the job search process in terms of post-hire outcomes, such as wages or job satisfaction. Whereas early research, mainly focussing on the U.S. labour market, found positive correlations between finding a job via social ties and post-hire outcomes, most recent studies reported inconclusive or even negative correlations. Country differences in the effectiveness of social ties could be explained by differences in the effectiveness of other search channels, e.g. public institutions. Therefore, this study contributes to the existing literature by investigating the effectiveness of social ties in the German labour market which is commonly regarded as rather strict and monitored by strong labour market institutions. Based on data from the German Socio-Economic Panel (SOEP), it is analysed whether wages, job satisfaction, and fluctuation are affected by the job finding channel. Furthermore, this is the first study which investigates whether job changes affect wage and job satisfaction differentials between the current and the previous job. Results show that finding a job via social ties is not related to higher income; yet, weak evidence can be found for higher job satisfaction and a reduction in turnover.
Keywords: J24; J28; J31; J63; 330; job search; social ties; wage; job satisfaction; turnover